Supramolecular nanofibers of natural asiaticoside for self-supporting gelation and enhanced transdermal delivery - Hu, Xixi; Tian, Shuang; Wang, Jiao; Luo, Weixi; Yao, Jiangli; Zhu, Rui; Dai, Yiyuan; Li, Hongyun; Ma, Yuhua; Liu, Chen; Wang, Wenping (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivesThe study aimed to develop a supramolecular hydrogel of asiaticoside (AS) via self-assembly and evaluate its potential for enhanced transdermal delivery.Materials and MethodsAS was dissolved in dimethyl sulfoxide (DMSO) and dispersed into a glycerol–water mixture (3:7 v/v) via ultrasonication to induce gelation. The critical gelation concentration (CGC) was determined through macroscopic and microscopic evaluation. Morphological analysis was performed using various microscopy techniques. Physicochemical properties were assessed using differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), Fourier-transform infrared (FTIR) spectroscopy, and UV–VIS spectroscopy. Molecular dynamics (MD) simulations with general AMBER force field (GAFF) parameters were used to analyze assembly dynamics. Rheological behavior and transdermal performance were tested using a rheometer and Franz diffusion cells, respectively.ResultsThe hydrogel formed at a CGC of 0.5% w/v, exhibiting pH-responsive gelation and a nanofibrous architecture. MD simulations revealed hydrogen bonding and π–π stacking as the dominant drivers of assembly, supported by FTIR peak shifts. The hydrogel demonstrated shear-thinning behavior (G’ > G″) and thermal stability below 70°C. Compared to the AS suspension, the hydrogel enhanced transdermal flux by 1.73-fold and skin retention by 2.04-fold, attributed to supersaturated drug molecules and sustained release from the nanofiber network.ConclusionThis work pioneers the use of AS as a natural supramolecular gelator, addressing its bioavailability challenges through nanostructured self-assembly. The hydrogel’s dual functionality (pH-responsive gelation and enhanced permeation) offers a sustainable platform for the transdermal delivery of hydrophobic phytochemicals, bridging phytochemistry and nanobiotechnology. This strategy expands the application of plant-derived saponins in advanced drug delivery systems.